An Efficient Fault-Tolerant Selection Strategy for Networks on Chip - Ashima Arora, Neeraj K Shukla , Harbinder Singh , Shaloo Kikan (International Journal of Advanced Science and Technology, 2020)
The NOC is the embedded communication framework that connects different IP cores in SOCs. Theadaptivity and sustainability of NOCs have reduced design time of new SOC based production. Althoughon chip networking is found to be an effective communication technique, any failures and faults in suchinfrastructure can affect IPs adversely. To deal with such a faulty situation, a route selection strategyaddressing faults on communication link is proposed. The proposed strategy while dealing with faults isalso bypassing the congested routes. The strategy when evaluated on network performance has shownan improvement in throughput and reduction in latency under different traffic profiles